Effect of high-risk sleep apnea on treatment-response to a tailored digital cognitive behavioral therapy for insomnia program: a quasi-experimental trial - Sweetman, Alexander; Reynolds, Chelsea; Lack, Leon; Vakulin, Andrew; Chai-Coetzer, Ching Li; Wallace, Douglas M.; Crawford, Megan; Richardson, Cele (Frontiers in Sleep, 2024)
Introduction: Therapist-delivered Cognitive Behavioral Therapy for Insomnia (CBTi) is an effective but largely inaccessible treatment for people with co-morbid Insomnia and sleep apnoea (COMISA).To increase CBTi access for COMISA, we aimed to develop a self-guided interactive 5-session digital CBTi program that is appropriate for people with insomnia-alone and COMISA, and compare its effectiveness between people with insomnia-alone, versus comorbid insomnia and high-risk sleep apnoea.Methods: Data from 62 adults with insomnia symptoms were used. High-risk sleep apnoea was defined as a score of ≥5 on the OSA50. Participants self-reported symptoms of insomnia (ISI), depression, anxiety, sleepiness (ESS), fatigue, and maladaptive sleep-related beliefs (DBAS-16) at baseline, 8-week, and 16-week follow-up. ESS scores were additionally assessed during each CBTi session. Intent-to-treat mixed models and complete-case chi 2 analyses were used.Results: There were more participants with insomnia-alone (n=43, age M[sd]=51.8[17.0], 86.1% female) than suspected COMISA (n=19, age=54.0[14.8], 73.7% female). There were no betweengroup differences in baseline questionnaire data, or rates of missing follow-up data. There were no significant group by time interactions on any outcomes. Main effects of time indicated moderate-tolarge and sustained improvements in insomnia (d=3.3), depression (d=1.2), anxiety (d=0.6), ESS (d=0.5), fatigue (d=1.2), and DBAS-16 symptoms (d=1.2) at 16-weeks. ESS scores did not increase significantly during any CBTi session.This interactive digital CBTi program is effective in people with insomnia-alone, and people with co-morbid insomnia and high-risk sleep apnoea. Further research is required to determine the effectiveness, safety and acceptability of digital CBTi in people with insomnia and confirmed sleep apnoea.